Late Onset Eating Disorders in Spain: Clinical Characteristics and Therapeutic Implications. Issue 1 (25th June 2013) - Bueno, B.; Krug, I.; Bulik, C.M.; Jiménez‐Murcia, S.; Granero, R.; Thornton, L.; Penelo, E.; Menchón, J.M.; Sánchez, I.; Tinahones, F.J.; Fernández‐Aranda, F.
<x xml:space="preserve">Abstract</x> Objective The literature on later age of onset (LAO) in women with eating disorders is scarce. We compared the severity of eating disorders, eating disorder subtype, and personality profiles in a clinical sample of consecutively assessed women with eating disorders with later age of onset (LAO, > = 25 years) to women with typical age of onset (TAO, <25 years). Method All eating disorder patients met the Diagnostic and Statistical Manual of Mental Disorders Fourth Edition (DSM‐IV) criteria and were admitted to the Eating Disorder Unit of the University Hospital of Bellvitge in Barcelona, Spain. Ninety‐six patients were classified as LAO and 759 as TAO. Assessment Measures included the Eating Attitude Test‐40 (EAT‐40), Eating Disorders Inventory‐2 (EDI‐2), Bulimic Investigatory Test Edinburgh (BITE), Symptom Checklist Revised (SCL‐90‐R), and the Temperament and Character Inventory‐Revised (TCI‐R), as well as other clinical and psychopathological indices. Results LAO individuals reported significantly fewer weekly vomiting episodes, fewer self‐harming behaviours, less drug abuse, and lower scores on the BITE symptoms, the EDI‐2 drive for thinness, and the TCI‐R harm avoidance scales than TAO individuals. Conversely, the LAO group reported more current and premorbid obesity than the TAO group. Conclusion LAO eating disorder patients in this sample presented with milder symptomatology and less extreme personality traits. Premorbid obesity may be more relevant to LAO than TAO eating disorders and should be routinely assessed and considered when planning treatment.